Organization and complexity of minicircle-encoded guide RNAs in Trypanosoma cruzi. - Avila, H A (1995)
The previously observed extensive sequence heterogeneity of the kinetoplast minicircle DNA in Trypanosoma cruzi, both intra- and interstrain, has raised the question as to how the minicircle DNA in this species can have any guide RNA (gRNA)-coding capacity at all, because there do not appear to be any variable-region sequences conserved between different strains. To address this question, we obtained the complete edited sequence of maxicircle unidentified reading frame 4 mRNA and identified 25 cognate gRNAs from gRNA libraries constructed from two clonal strains of T. cruzi--Sylvio X10/CL1 and CAN III/CL1. Libraries of PCR-amplified minicircle-variable regions were also constructed for both strains. A single gene for each gRNA was identified in the same polarity within specific minicircle-variable regions from both strains, 60-100 nt downstream from the conserved 12mer sequence. GTP-capped total gRNA from one strain failed to cross-hybridize with minicircle DNA from the other strain. The explanation for this proved to be the number of polymorphisms, mainly transitions, within the homologous gRNAs in the two strains. In most cases, these transitions did not destroy the edited mRNA/gRNA base pairing, as a result of the allowed G-U wobble base pairing. The sequences of the variable regions containing homologous gRNAs in the two strains probably derived from an ancestral sequence, and each has accumulated sufficient polymorphisms so as not to allow hybridization. Within a strain, multiple redundant gRNAs were identified that encode identical editing information but have different sequences.